Prevalence of behavioral disorders in children and early adolescent: An Eastern Indian single center study - Biswas, Rupa; Biswas, Payel; Das, Gargi; Saha, Jinia; Banerjee, Shyamal; Ghosh, Srijit (Asian Journal of Medical Sciences, 2022)
Background: Mental health problems evolving from early childhood to adolescent period affect the processes of adaptation and capability in adulthood. Aims and Objectives: The study aims to study the prevalence of different types of behavioral disorders among children and early adolescents (6–12 years) and detect association between socio-demographic parameters and behavioral disorders as well as detect the behavioral problems for early treatment regarding their child’s behavioral problem. Materials and Methods: A cross-sectional retrospective study was conducted in the pediatric OPD and Adolescent Clinic of Calcutta National Medical College from March 2019 to February 2020. 176 patients were included after proper sampling and consent. Semi-structured socio-demographic profile sheet was filled up by parents. Individual child was assessed for various behavioral disorders using the Child Symptom Inventory (CSI)-4 parent questionnaire where data were collected from parents by the investigator through a single time interview. Results: Prevalence of Anxiety disorders was highest in our study, with increased incidence in females. Autism in children was found to be associated with their low birth weight. High incidence of disruptive, impulse control and conduct disorder was seen among boys and mainly in children living with single parent and mothers working. Conclusion: The study is based on informants’ perceptions of the children’s behavior. The study enables understanding of the behavior of children and associated contexts which is essential to make an interventional plan tailored to the needs of the child in the long run.